(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
Introduction The concept of wellness has long been associated with a holistic viewpoint, encompassing various dimensions such as the mind, body, spirit, and social interactions within a community. The COVID-19 pandemic has brought forth unprecedented challenges, further underscoring the importance of addressing mental health, learning disruptions, social well-being, and physical health concerns within individuals. This study delved into the holistic wellness of senior high school students during the school year 2021-2022, aiming to provide a foundation for crafting a student-led comprehensive wellness plan for Senior High School. Methodology A descriptive-comparative research design was employed to gather data from 137 randomly selected Grade 11 and Grade 12 students enrolled at Union Christian College during the aforementioned school year. The research instrument utilized was an adapted Canfield (2017) questionnaire designed to assess overall health and well-being across physical and environmental health, mental and emotional health, and social and spiritual health dimensions. Respondents’ holistic wellness was then analyzed, considering various demographic profiles. Results The analysis of the respondents’ profiles revealed a higher representation of females than males, with family incomes predominantly below P20,000.00 and a majority adhering to the Roman Catholic faith. The respondents generally exhibited good well-being levels across the three dimensions of wellness – physical and environmental, mental and emotional, and social and spiritual. Notably, the study observed a decline in mental-emotional and socio-spiritual health during the pandemic, while physical and environmental health showed improvement. On the whole, respondents’ holistic wellness was rated as good. Significant variations emerged when comparing physical-environmental and socio-spiritual health before and during the pandemic. Mental and emotional health, however, displayed a consistent pattern. Additionally, the respondents’ profiles in terms of gender, family monthly income, and church affiliation significantly correlated with the extent of their wellness. The findings show that most respondents were female students, belonging to families with income levels above the poverty line and identifying as Roman Catholic. The students exhibited favorable levels of physical and environmental, mental and emotional, and social and spiritual wellness. The study suggests that these profiles significantly influence wellness before and during the pandemic. As a recommendation, the study proposes implementing a Holistic Wellness Plan for Senior High School students, acknowledging the multifaceted nature of their well-being. Discussion The study underscores the essential need for a comprehensive wellness approach, especially in a disruptive event like the COVID-19 pandemic. The observed shifts in wellness dimensions reflect the pandemic’s distinct impacts on various facets of students’ lives. The significance of gender, family income, and religious affiliation in wellness highlights the role of social determinants in shaping individuals’ well-being. The proposed student-led Holistic Wellness Plan addresses immediate concerns and fosters a proactive approach to sustaining well-being. By integrating physical, mental, emotional, and spiritual aspects, the plan can cater to the diverse needs of students. This approach aligns with the core philosophy of holistic wellness, emphasizing the interconnectedness of different dimensions in promoting overall health and flourishing. In conclusion, this study contributes valuable insights into the holistic wellness of senior high school students within the challenging context of the COVID-19 pandemic. By recognizing the multifaceted nature of well-being and considering the influence of demographic factors, educators and institutions can better tailor interventions to support students in achieving and maintaining optimal holistic wellness.